Formation of tunable graphene oxide coating with high adhesion. Issue 7 (27th January 2016) - Lin, Liangxu; Wu, Huaping; Green, Stephen J.; Crompton, Joanna; Zhang, Shaowei; Horsell, David W.
Abstract : Graphene oxide (GO) can form a highly adhered robust coating on nickel–aluminum–bronze (NAB) using a conceptual process (the formation and consolidation of a layer of GO), which allows further functionalisation of the coating for various potential applications. Abstract : Graphene oxide (GO) can be applied as a coating on metals, but few of these coatings have an adhesion suitable for practical applications. We demonstrate here how to form a GO coating on metals with a high adhesion (∼10.6 MPa) and tuneable surface, which can be further applied using similar/modified techniques for special applications ( e.g. anti-corrosion and anti-biofouling).